Cultivation of Processed Ginger Immunity (IJO) Program as Herbal Medicine for Residents in Probolinggo - Masluha, Siti; Rahmansyah, Ahmad Iskandar; Nabil, Muhammad; Hidayati, Febtri Darma (IMPOWERMENT SOCIETY, 2022)
Incentive use of family medicinal plants can increase body immunity and accumulate harmful residues in the environment. Family medicinal plants are natural alternatives in maintaining immunity, one of which is the use of ginger plants. This community service aims to characterize and determine the local biological potential (ginger) as an immune enhancer. This program consists of two parts, namely counseling which contains about how to maintain the body's immunity with processed ginger, and practices that teach how to grow ginger by utilizing a narrow land. With the procurement of the IJO (Processed Ginger Immunity) program in the Pakistaji sub-district, it is hoped that the community will be aware of the importance of environmentally friendly herbal medicines.